PERILAKU PEDULI LINGKUNGAN SISWA DI SMPN 1 TANJUNGSIANG SEBAGAI SEKOLAH ADIWIYATA - Sindi Sari Puspita, - (2021)
To realize education in the environment, the government is making efforts by making environment-based education through Adiwiyata schools. Education that takes place in Adiwiyata schools uses the environment as an effort to shape school members who care and have an environmental culture. The main activity of the Adiwiyata school is directed at the realization of the school institution as the background for this research, in this case the focus of the research is the environmental care behavior of students at SMPN 1 Tanjungsiang as an Adiwiyata school. In general, this study wants to find out whether the environmental care behavior is in line with the predicate of SMPN 1 Tanjungsiang as a Adiwiyata school. The method used is descriptive statistical analysis study, namely, a research method carried out with the main objective of making an objective description or description of a situation and how or why the phenomenon occurs. The data analysis technique used is using percentage calculations. With various factors that influence the environmental care behavior of students at SMPN 1 Tanjungsiang in the students' knowledge of environmental care behavior by disposing of garbage according to the category of grouping garbage properly and correctly, then the attitude of environmental care behavior properly, then motivation or encouragement to behave caring for the environment students of SMPN 1 Tanjungsiang and the effectiveness of students' perceptions of environmental care behavior.